Listeria monocytogenes in Almond Meal: Desiccation Stability and Isothermal Inactivation - Meijun Zhu; Xia Song; Xiaoye Shen; Juming Tang (Frontiers in Microbiology, 2020)
Almond are among the most consumed tree nuts and used in a variety of food products. Recent almond butter recalls due to potential contamination of Listeria monocytogenes highlight the need to control L. monocytogenes in almond products. The objectives of this study were to examine the stability of L. monocytogenes in almond meal during extended storage and analyze thermal resistance of L. monocytogenes in almond meal of controlled moisture contents or water activity (aw) using thermal death time (TDT) cells and thermal water activity (TWA) cells, respectively. L. monocytogenes maintained a stable population in almond meal for 44–48 weeks at 4°C regardless of aw; however, we observed about 1.69 and 2.14 log10 colony-forming units (CFU)/g reduction of L. monocytogenes in aw 0.25 and 0.45 almond meal over 44 to 48 weeks of storage at 22°C. Under all test conditions using either TDT or TWA cells, the inactivation kinetics of L. monocytogenes in almond meal fitted the log-linear model well; thermal resistance of L. monocytogenes in almond meal was inversely related to the aw of samples. D75-/D80-values of L. monocytogenes in aw 0.25 and 0.45 almond meal obtained using TDT cells were 47.6/22.0 versus 17.2/11.0 min, respectively. D80-, D85-, and D90-values of L. monocytogenes in aw 0.25 almond meal obtained using TWA cells were 59.5 ± 2.1, 27.7 ± 0.7, and 13.2 ± 1.1 min, respectively, in contrast to 22.0 ± 1.1, 10.6 ± 0.2, and 4.6 ± 0.4 min obtained using TDT cells. The z-value of L. monocytogenes in aw 0.25 almond meal was not affected by TWA and TDT cell type (15.4–15.5°C), whereas z-value of L. monocytogenes in aw 0.45 almond meal was 10°C higher than that in aw 0.25 almond meal. This study contributes to our understanding of L. monocytogenes in nuts and impacts of aw on the development of thermal resistance in low-moisture foods.